Hubungan Dukungan Sosial dengan Burnout pada Perawat Rawat Inap RSUD Muntilan Magelang - Matussilmiyuliyani, Ida; Widiyanto, Puguh; Masithoh, Robiul Fitri (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Nurses are one of the health workers from hospital services who are the benchmark in determining the quality of hospital services. The nurse's task in helping and restoring the patient's condition must be in accordance with hospital standards so that it requires nurses to have sufficient health and energy. This condition can deplete the nurse's physical and emotional strength which causes burnout. Burnout that occurred at the Muntilan Hospital Magelang in 2019 was high. This burnout will affect the performance of nurses, causing the problem of decreasing the quality of hospital services. One of the efforts to improve the quality of service is to increase the work motivation of nurses. High work motivation will affect the performance of nurses. Good nurse performance has positive behavior that is able to support individual performance and organizational performance to improve better services. High social support will improve nurse performance. Aim : the goal in the study is to identify social suport with burnout in the RSUD Muntilan Magelang hospital. Method : the method in this study is a cross sectional survey with a quantitative design. The sample in this study were 45 nurses that are divided into 5 inpatient wards. Sampling used stratified random sampling. Collecting data in this study using a questionnaire via google form. In this study the data were statistically analyzed using the Spearman rank test. Results: Spearman rank test on the relationship of social support obtained a significance value of burnout of p = 0.233 (p>0.05) Conclusion: there is no significant correlation between social support and burnout in nurses in the inpatient room at Muntilan Hospital, Magelang Regency. There is no correlation between social support and burnout, but clinically, social support is still needed to anticipate burnout.